“We are the battlefield”: conflicting knowledge and baroque transgressions in El pez de oro (Revista de Crítica Literaria Latinoamericana, 2010)
This article tackles the study of El pez de oro (1957), by Gamaliel Churata, from a perspective that strives to take into account its heterogeneous elements. Churata’s text is eloquent in its denunciation of colonialism; yet, its complexity presents a series of challenges to interpretation. A possible route, which is explored here, goes beyond its connections with Andean religious thought, indigenismo and the avant-garde, and links El pez de oro with the Latin American Baroque cultural production.
Keywords: Gamaliel Churata; indigenismo; Latin American Baroque; heterogeneous literature; Peruvian literature